Building Conceptions of Cognitive Enhancement: University Students' Views on the Effects of Pharmacological Cognitive Enhancers. (12th May 2019) - London-Nadeau, Kira; Chan, Priscilla; Wood, Suzanne
Abstract: Background: Use of prescription stimulants for cognitive enhancement in healthy individuals has been of growing interest to the academic community. University students can be prone to use these pharmacological cognitive enhancers (PCEs) for their perceived academic benefits. Objectives: We aimed to understand university students' beliefs about the factors influencing PCE use, the cognitive and health effects of the drugs, and how these conceptions are interrelated. Methods: Data were collected through focus groups with 45 students at the University of Toronto in 2015/2016. We used thematic analysis to extract key themes and cooccurrence coefficients to evaluate the overlap between these themes. Results : We found that participants perceived users as either struggling students or high-achieving ones. Alleged benefits of PCEs included enhanced focus, attention, memorization, and grades, but did not include increased intelligence or long-term cognitive enhancement. Participants disagreed on whether ADHD diagnosis would affect how PCEs worked and how "needing the drug" was determined. Mentions of nonspecific side effects were common, as was the possibility of misuse (e.g., addiction, abuse). Though not an initial aim of the study, we uncovered patterns pertaining to whom participants used as sources of information about different themes. We propose that social learning theory provides a useful framework to explain how the experiences of peers may shape the conceptions of our participants. Conclusions/Importance : Our findings highlight that conceptions surrounding PCEs are multileveled, and informed by a variety of sources, including peers. This should be considered in the development of interventions geared toward university students.